2016
DOI: 10.1093/schbul/sbw090
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Intellectual Functioning and Cognitive Performance to Brain Structure in Schizophrenia

Abstract: These data provide additional evidence for heterogeneity in SZ. Impairments in cognition associated with reduced ePMC-IQ were related to evidence of broad brain structural alterations, including suggestion of early cerebral disruption. In contrast, impaired cognitive functioning in the context of more intact intellectual functioning was associated with cortical alterations that may reflect neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 34 publications
5
59
0
Order By: Relevance
“…We did not find a correlation between EVM and TNF-α or IL-6, but these cytokines may be correlated to other cognitive domains. Second, we did not measure other cytokines such as IL-1β and eotaxin [42, 43]. Furthermore, we did not analyze the potential influence of antipsychotics on cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a correlation between EVM and TNF-α or IL-6, but these cytokines may be correlated to other cognitive domains. Second, we did not measure other cytokines such as IL-1β and eotaxin [42, 43]. Furthermore, we did not analyze the potential influence of antipsychotics on cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…showed that patients with schizophrenia with a compromised IQ had smaller‐than‐normal total brain volume, intracranial volume, total brain volume corrected for intracranial volume, cortical gray matter volume, cortical thickness, and insula volume. They also reported that patients with schizophrenia with a preserved IQ showed reduced cortical gray matter volume and cortical thickness . Weinberg et al .…”
mentioning
confidence: 96%
“…This variability seems to suggest potential heterogeneity in the neuropathology of schizophrenia based on cognitive status. Furthermore, the following two studies reported that there were different alterations in brain structures in patients with schizophrenia classified according to these cognitive subgroups . Czepielewski et al .…”
mentioning
confidence: 99%
“…Our present results reveal novel associations between eye‐movement measures and cortical thickness of the left pars opercularis in SCZ. Eye movements are known to be associated with Wechsler Adult Intelligence Scale (WAIS)‐III measures and cortical thickness alterations have been linked to changes of intellectual functioning in SCZ . After controlling for further factors related to intelligence and education (education, estimated premorbid IQ, and WAIS‐III full‐scale IQ), these correlations were weakened (integrated eye‐movement score, R = 0.23, p = 2.63 × 10 −2 ; scanpath length, R = 0.26, p = 1.28 × 10 −2 ; see Table S4 for full results in participants with SCZ and Table S5 for results in healthy controls).…”
mentioning
confidence: 99%